Conservation and production impacts of soil and water conservation practices under different socio-economic and biophysical setting: a review - Amsalu Tilahun; Fenet Belay (Brawijaya University, 2019)
In Ethiopia, the increase in land degradation mainly in the form of soil erosion necessitates implementation of soil and water conservation (SWC) practices. So far impact evaluation studies are scattered and not comprehensive. In this paper detailed quantitative review of impact of SWC practices under different climate and socio-economic setting were done on runoff, soil loss, siltation, soil fertility and crop yield. Up to 1980s, expert and government considered reduction of soil loss and runoff as big achievement. This was not in line with the interest of subsistence farmers who need short term benefit. The reduction of soil loss, runoff and siltation of reservoirs are positively acknowledged by majority researchers and have several beneficial effects: increase soil moisture content, groundwater recharge, increased in situ sediment deposition, making the hill slope suitable for agriculture and reduce siltation. Regarding production objective, SWC practices have mixed impact (positive and negative) on crop yield and soil fertility. In this review it was found that 62.5% of the reviewed materials revealed that SWC measures have positive impact on soil fertility either in increasing or maintaining. In contrast, 25% showed SWC treated areas had lower soil fertility than untreated and 12.5% showed no significant change in soil fertility. In summary, the impact of SWC practices especially on soil fertility and crop yield varies depending on soil erosion degree before SWC implemented, design of SWC measures, crops, plows, socio-economic, soils types and climate mainly rainfall. The review in detail discussed why SWC practices have variation in impact on soil fertility and crop yield. Finally SWC practices are an action of no option for sustainable development and food security under current soil erosion and climate change.